Energy Generation using Magnetic Repulsion - Shivarudra Swamy, R.; N.S, Jayalakshmi.; Kumar, Mohit; ., Ujawal (International Journal of Engineering and Technology, 2018)
This paper proposes a novel technology to convert the magnetic repulsive force available from permanent magnets to electrical energy using repulsion magnet technique. The proposed technology employs the theory of magnetic repulsion to generate the electricity. The system uses permanent magnets to produce repulsion and this repulsive force produces a torque, which drives a DC generator. The repulsive magnetic V channel consists of repulsive magnetic line of forces. The two channels repel each other, which create a force in the forward direction. The bullet magnet that is used is inserted into the channel and passed through a repulsive barrier and ultimately is placed in the repulsive part of the magnetic _field lines that shoots the bullet in forward direction. A belt coupler is coupled with the bullet and wrapped in the rotor of the dynamo. The torque produced by the repulsive forces will ultimately drive the dynamo, which will result, to electricity generation. It is almost free energy as the energy input is quite low and efficiency will be very high. This model requires no electrical input and works only on the forces of nature.Â Â